2019
DOI: 10.3889/oamjms.2019.243
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Ketorolac versus Nalbuphine in Relieving Postoperative Pain after Tonsillectomy in Children

Abstract: BACKGROUND: Pain is a major postoperative complication worldwide, which in turn impairs normal body performance and increases postoperative morbidity, hospitalisation, and the susceptibility to infections which also lead to chronic pain development. AIM: The purpose of this study was to evaluate the efficacy of intravenous ketorolac versus nalbuphine as analgesia after adenotonsillectomy surgery to determine the optimal procedure for pain control and postoperative reduction of analgesic use. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
2
Order By: Relevance
“…Nalbuphine is a potentanalgesic agent that is similar to morphine [27,28]. Studies have shown that nalbuphineis widely used in pain management during the perioperative period [29,33,34,35]. Our results showed that nalbuphine was as effective as fentanyl in reducing pain-induced patient movement, and there was no difference in dosage.…”
Section: Discussionmentioning
confidence: 55%
“…Nalbuphine is a potentanalgesic agent that is similar to morphine [27,28]. Studies have shown that nalbuphineis widely used in pain management during the perioperative period [29,33,34,35]. Our results showed that nalbuphine was as effective as fentanyl in reducing pain-induced patient movement, and there was no difference in dosage.…”
Section: Discussionmentioning
confidence: 55%
“…A total of 189 randomized controlled and comparison trials met the inclusion criteria for analysis 18–206 . A PRISMA diagram outlining the literature search is shown in Figure 1, and the risk of bias graph is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 189 randomized controlled and comparison trials met the inclusion criteria for analysis. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ...…”
Section: Resultsunclassified
“…Ketorolak diketahui dapat menurunkan nyeri pasca operasi dan menunjukkan insidensi sedasi yang lebih rendah dibandingkan dengan petidin [14][15][16] . Berdasarkan penelitian, efek analgetik ketorolak lebih baik dibandingkan dengan tramadol dan nalbupin 17,18 . Nalbupin diketahui lebih efektif dibandingkan tramadol, namun tidak lebih efektif dibandingkan fentanil 19,20 .…”
Section: Pendahuluanunclassified